(untitled) (Journal of the Bangladesh Agricultural University, 2014)
This experiment was conducted to evaluate the response of tobacco yield under different irrigation practices and tobacco varieties during November 2012 to April 2013 (Rabi season) at Paharpur village of Kushtia district. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Four treatments were T0 (control, no irrigation), T1 (traditional practice; 13 cm irrigation water applied), T2 (10 cm irrigation water applied) and T3 (5 cm irrigation water applied). Three tobacco varieties were used for the experiment viz. V1 (NC 95), V2 (K 326) and V3 (CS 447). All necessary data on yield and yield contributing characters including irrigation were collected from experimental plots. Irrigation treatments showed significant effects on yield and yield contributing characters of tobacco. Results revealed that the highest cured leaf yield (3.83 t ha-1) was obtained in treatment T2 followed by T3 (3.46 t ha-1) and T1 (3.07 t ha-1). The highest and lowest yield were obtained as 5.05 t ha-1 and 2.85 t ha-1 for the interactions T2V2 and T1V1, respectively. Highest water productivity (63.92 kg/ha/cm) was found in treatment T3. Among three tobacco varieties, V2 (K 326) gave highest yield followed by V3 (CS 447) and V1 (NC 95) as 3.17, 2.38 and 2.22 t ha-1, respectively. Therefore, application of 10 cm irrigation water on the variety K 326 can be the promising practice for cultivation of tobacco. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21408 J. Bangladesh Agril. Univ. 12(1): 171-176, June 2014